Solids spectroscopy with applying explosion energy - Plotnikov, S.V.; Oleshko, V.I. (Recent Contributions to Physics, 2017)
For the purposes of geochemistry and environmental studies, it is interest to establish systems that allow the elemental analysis of the solid phase itself. Modern instruments using inductively coupled plasma for emission spectrometry and for mass spectrometry are designed for analysis of solutions and have significant limitations on the concentration of impurities. Dissolution process of geological samples is a laborious and complex process due to the wide variety of composition and the large number of analyzed elements that geochemists are interested in. The possibility of using the explosion energy of condensed explosives in solids analytical spectroscopy was investigated. For the atomization and excitation, emission spectra of solids (Al2O3) were used pressed powders of furazanotetrazinedioxide (FTDO, C2N6O3). Initiation of the explosion was induced by the influence of high-current electron beam. The impurity atoms that are the part of FTDO, as well as atoms and molecules formed by the evaporation of Al2O3 were identified in the spectra of explosion plasma.